Establishment of Hematological Reference intervals for healthy Children in Elobied City, Sudan - Tarig Osman Khalafallah Ahmed; Malaz Elfatih Abd-elkareem Ahmed; Ream Elzain Abdelgadir; Hiba Awadelkareem Osman Fadl; Assad MA. Babker (Journal La Medihealtico, 2021)
Hemogram Reference intervals are established since a healthy population is critical to accurately interpret laboratory tests, which include Hemoglobin estimation, Red blood cells count and indices, White blood cells count and differential in addition to Platelets count. This study aims to establish the reference interval of the complete hemogram amongst healthy Sudanese children in Elobied city, Sudan. A descriptive cross-sectional study included 354 healthy children, aged between 3 to 17 years, who were categorized into three groups according to age. A questionnaire was fulfilled, EDTA anti-coagulated venous blood sample was collected from each child then the complete hemogram was performed automated hematological analyzer (Sysmex Xp 300), Finally, Data was analyzed by a software program (SPSS version 21). The hematological reference intervals for healthy children [Hb g/dl, HCT%, RBCs count x106μL, MCV/fL ,MCH /pg., MCHC g/dl ,WBCs count x10³/μL, Neutrophil count%, Eosinophil count %, Basophile count %, lymphocyte count ,Monocytes count%, RDW CV and PLTs count×10³/μL] are [(12.4±1.2),(37±4),(5.0 ±0.4), (82±5.0), (26±3.0), (32±3.0) ,(7.0±2.0) (47±10), (1±0.1) ,(0±0),(45± 10),(7 ± 4), (13±1.8) &(227±91)] respectively. The hematological RI for healthy children in Elobied was established in this study to be representative of this population, there was a significant gender-based difference in all the evaluated hematological parameters, they were found to be higher in males than in females except for basophil (%). Finally, the results of this study would shed a light on the importance of establishing RI for the children population in Elobied.